(untitled) (Academia Science Repository, 2023)
The importance of "Saqibulbul" epic in popularizing the art of giving among students is incomparable. In the article, the friendship between Saqibulbul and Goroglibek was shown in the true sense. Symbols of motherhood are illuminated. Khushvakt Bakhsh’s epic skill is clearly visible. It is of great educational and spiritual importance for young students.